Exploring the effectiveness of DMFonF on English vocabulary and grammatical plural constructions among Malaysian preschoolers - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno; Kawaguchi, Satomi; Syed Uzir, Sharifah Fatin Athira (UKM Press, 2023)
This study explores the effectiveness of a novel second language instruction approach in a Malaysian preschool context. This approach is called Developmentally Moderated Focus-on-Form (DMFonF), an instructional intervention that integrates a communicative approach to second language teaching with a ‘focus on form’ and a psycholinguistic theory of second language development, the Processability Theory. In this study, the development of six Malaysian preschool children (mean age =5.6) were investigated in a 10-week longitudinal study. Three children in the group received DMFonF in their English lessons and the other three children received no intervention. Data collection sessions were conducted at three different points over the 10 weeks to evaluate the children’s English development. The first data collection point, a pre-test, was conducted physically before the DMFonF intervention to establish the lexical and grammatical baseline of the children’s English development. The second data collection was conducted online after the first set of six face-to-face lessons with DMFonF. The third and final data set was also collected online after the completion of the second set of four online lessons. Results show that the children who received DMFonF instruction acquired English lexical and grammatical plural constructions, specifically the plural suffix -s and the plural noun phrase agreement (i.e., numeral quantifiers+ noun+ suffix-s) as taught in the DMFonF lessons; the children in the control group, however, acquired English lexical items but their grammatical skills did not change. The outcome of this study suggests that DMFonF is effective in triggering grammatical development and in further facilitating the learners’ lexical acquisition.